Pengaruh Parameter Motor pada Sistem Kendali tanpa Sensor Putaran - Bernadeta Wuri Harini (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2021)
In controlling permanent magnet synchronous motor (PMSM) without using a rotation sensor (sensorless control), some motor parameter data is needed. Among the motor parameters used in the control are stator resistance, inductance, and magnetic flux. This paper will analyze the effect of these parameter values ​​in sensorless motor control. The parameter values ​​will be varied so that the motor parameter values ​​in the controller are different from the actual motor parameter values. The percentage of variation for each parameter varies depending on the influence of these parameters on control. The desired motor speed is 100 rad / second with controlling constants KP = 0.5, KI = 0.9, and KD = 100. The controller gain values ​​(KP, KI, and KD) are obtained by the heuristic tuning method. Simulations are carried out for several differences in parameter values ​​using Simulink. From the simulation results, it is found that the motor parameter values ​​of the controller that are not the same as the actual motor parameter values ​​will affect the control process. The difference in the motor parameter value between the controller and the actual value causes the motor not to rotate as the desired value.